Ο εθνικιστικός πολιτικός λόγος: Συγκριτική ανάλυση των λόγων της Μαρίν Λεπέν και του Νικόλαου Μιχαλολιάκου - (:unkn) unknown (My University, 2019)
The objective of this paper is to present the power of the nationalist political discourse and the exposition and discussion of the means of persuasion and manipulation of the people. While the progressive rise of the far-right wing ideology has been raising concerns the past years, the main attempt of this paper is to study the causes of this phenomenon in relation to the language possibilities and the strategies that can be followed to achieve their objectives. The study of multiple speeches both in Greek and in French aims to present the behaviour of language under dissimilar linguistic environments. The different cultural and linguistic perspective of the two politicians offers the possibility to search the pattern of the rhetoric devices used in extreme right political speeches and reach more objective and universal conclusions. The final aim is to contribute in raising peoples’ awareness on political discourse manipulation and further more contemplate the magnitude of the power of words independently of the language nature and the geographic boarders.
Keywords: ανάλυση πολιτικού λόγου, εθνικισμός, ακροδεξιά, λαϊκισμός, ρητορική, έθνος; Political Discourse Analysis, nationalism, populism, rhetoric devices, far right wing